A group of research analysing the feet of people with rheumatoid arthritis - Ramos Petersen, Laura (UMA Editorial, 2021)
Rheumatoid arthritis (RA) shows high prevalence and morbidity worldwide and its biggest impact can be observed in the small joints of the hands and feet. Pharmacological and other non-pharmacological interventions such as foot orthoses can play an important role in managing foot pathologies in patients whose systemic disease is controlled. However, the current situation is that there is a lack of qualitative and quantitative research to provide enough information about this topic. Furthermore, reliable and valid tools to assess the disease and interventions effect are vital to assess the effect that RA has on the feet. This thesis comprises six separate studies: first, four quantitative studies were performed to help to understand the potential role of RA and RA treatments on patients’ feet. Next, a protocol was developed to compare physical activity, general and foot health and foot health experiences in patients with RA when wearing three different types of foot orthoses. Finally, a qualitative study aimed at understanding the RA patients' experiences before and after wearing foot orthoses for 6 months. The findings of the quantitative and qualitative studies focused on foot orthoses suggest that the use of foot orthoses alleviate foot pain, reduce disability and improve physical activity. The systematic review which evaluates biologics on RA patients’ feet shows that postoperative surgical site infection or delayed wound healing were not associated with biologics use. Furthermore, the Self-Reported Foot and Ankle Score questionnaire presents acceptable methodological quality to assess the foot and ankle in patients with RA. Taken together, the results of this work show that foot orthoses are effective in the management of foot pain in patients with RA, reducing disability and improving physical activity. Some valid questionnaires are available to assess the disease and interventions effect in terms of foot and ankle, especially in clinical practice.
Keywords: Artritis reumatoide - Tesis doctorales; Pies - Enfermedades - Tesis doctorales; Rheumatoid arthritis; Foot; Pie